Метод розрахунку радіусів отворів багатоелементного напрямленого відгалужувача - Зайченко, Н. Я. (ХНУРЕ, 2022)
This work is devoted to directional couplers parameter calculation and verification by simulation in HFSS. The contradiction between the results of previous calculations and modeling is the problem of this research. A simplified method is proposed for calculating the radii of the holes of a directional coupler, which consists in central hole radii calculating, on the basis of the parameter of required coupling, which differs by using the Newton binomial coefficient, so the radius of the current hole is calculated as the radius of the central hole which is divided by coefficient. The coefficient is the cube root of the of the binomial polynomial numbers ratio, where polynomial numbers correspond to central and current hole. The cube root of number is a value which when multiplied by itself thrice or three times produces the original value.